Management of Islamic Education in the Challenges of Society 5.0 - Abdullah Haq Resufle; Moh Rofiki (Universitas Pahlawan Tuanku Tambusai, 2022)
Today, Islamic education is faced with challenges in welcoming the society 5.0. The challenge is to focus more on improving human resources because the society 5.0 places humans as the main component. Therefore, it is very important in the management of Islamic education to always exist and face the challenges of the society 5.0. This research is a literature study that interprets the data in a descriptive analysis. This study aims to see and examine the problems and challenges and the strategies used by Islamic education management in facing the society 5.0. The study results show that the problems and challenges of Islamic education management related to human resources are the lack of adequate resources and the main competencies that individuals must possess, namely: creativity, critical thinking, communication, and collaboration. The Islamic education management strategy in facing the society 5.0 is to prepare human resources who have digital abilities and are innovative and creative thinkers; change the paradigm of educational institutions, and prepare leaders of educational institutions who have leadership qualities and can collaborate so that the demands for life skills needs in the 21st century are achieved